PEMANFAATAN TEKNOLOGI INFORMASI DAN METODE CRAFT DALAM PENINGKATAN KESUKSESAN BELAJAR GENARASI MILENIAL - Syah, Firdiyan; Riyadi, Ahmad (Jurnal Berdaya Mandiri, 2023)
Low motivation to learn is often considered as the cause of the low quality of graduates of a tertiary institution. This factor even raises a dilemma, because with low learning motivation, students cannot master learning materials properly, but must graduate for the sake of the continuity of the college. Practices like this are safe and lasting, because the majority of students just want to get a bachelor's degree, and not to master science. Meanwhile, many tertiary institutions apply the concept of customer satisfaction in the world of education, making it easier for students to graduate to be considered as providing satisfaction to their consumers (students). Responding to challenges in the world of education today in community service is able to provide and motivate and how to gain knowledge through information technology. The CRAFT method is a self-image programming method introduced by the psychocybernatic technique. This method is a structured method of controlling the soul and the individual. The CRAFT method consists of Cancel, Replace, Affirmation, Focus and Training. The application of the CRAFT method is accompanied by the Mind Mapping technique. In this technique students are required to determine goals, plans and actions. We also certainly know that the benefits of mind mapping are for teaching and learning. The end result of the CRAFT method is being able to increase enthusiasm for learning through motivation and assistance on how to get good knowledge through information technology.